2007
DOI: 10.1007/s10508-007-9195-y
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Decisional Balance Intervention Increases Motivation and Behavior Regarding Condom Use in High-risk Heterosexual College Men

Abstract: Male college students constitute one of a number of at-risk populations susceptible to receiving and transferring sexually transmitted infections. Interventions designed to increase condom use have produced mixed results, but increasing motivation to use condoms may decrease risky sexual behavior. The current study examined the decisional balance, a component of Motivational Interviewing (MI), as an intervention to promote condom use. A total of 41 college men at-risk for negative outcomes from both unsafe sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The majority (26/29) of the included studies were conducted in state-run mainstream middle and high schools, with two conducted in colleges 7,8 and one in a university setting. 9 Although descriptions of study populations were not always comprehensive, and did not describe socio-economic status, several studies were conducted within locations where the majority of participants were from a particular population subgroup such as African American, 10e12 Black, 13,14 Hispanic, 15 or a combination of these, 16e22 also including Latino.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (26/29) of the included studies were conducted in state-run mainstream middle and high schools, with two conducted in colleges 7,8 and one in a university setting. 9 Although descriptions of study populations were not always comprehensive, and did not describe socio-economic status, several studies were conducted within locations where the majority of participants were from a particular population subgroup such as African American, 10e12 Black, 13,14 Hispanic, 15 or a combination of these, 16e22 also including Latino.…”
Section: Resultsmentioning
confidence: 99%
“…No control data is given. 7 In the second study four workshop style interventions increased contraceptive knowledge compared to the control, and those receiving the experimentally oriented intervention showed significantly more positive change in contraceptive attitudes and intention to use, and reported use of birth control than all other groups. 8 Interventions Which are Part of Curriculum Interventions In addition we identified several studies which reported on large interventions primarily focused on classroom based sexual health education lessons but which had additional components relevant to this review (four CBA).…”
Section: Interventions To Increase Contraceptive Provision and Use Inmentioning
confidence: 90%
“…The concept of Decisional Balance refers to a procedure derived from Janis and Mann's (1977) decisionmaking model, assumes that some decision making involves careful scanning of all relevant considerations that enter into a "Decisional Balance" sheet of comparative potential gains and losses (cf. LaBrie, Pedersen, Thompson, & Earleywine, 2008). Individuals that intend to help will list alternatives, efforts and the consequences of the actions, and if the downside outweigh the benefits, then they will be less likely to do it.…”
Section: Decisional Balancementioning
confidence: 99%
“…For example, if an individual is going to stop a person larger than himself alone, the success rate will be lower than when he had companies, thus hindering the likelihood of him helping. As an often important component of many motivational interventions, the Decisional Balance penetrates a participant's state of ambivalence, clarifies competing motivational factors, and encourage the person to consider change (LaBrie, Pedersen, Thompson & Earleywine, 2008). In this study, we seek to understand whether listing and weighing the benefits (the pros) and loss (the cons) of intervening before intervening results in active helping behavior.…”
Section: Decisional Balancementioning
confidence: 99%
“…Four studies have reported the use of the decisional balance exercise to be predictive of substance use reductions (LaBrie et al, 2006(LaBrie et al, , 2008McNally et al, 2005;Strang and McCambridge, 2004).…”
Section: Abstract Objectivementioning
confidence: 99%